The Impact of Aortic Valvular Calcium on Transcatheter Heart Valve Distortion. (5th January 2021) - Nakajima, Akihiro; Naganuma, Toru; Yuki, Haruhito; Onishi, Hirokazu; Amano, Tatsuya; Yabushita, Hiroto; Kawamoto, Hiroyoshi; Mitomo, Satoru; Kitanaka, Yosuke; Nakao, Tatsuya; Kurita, Naoyuki; Ishiguro, Hisaaki; et al.
Abstract : Objectives . To investigate the relationship between the eccentric calcification of aortic valve and transcatheter heart valve (THV) distortion and the impact of THV distortion on echo parameters and clinical outcomes. Background . The effects of eccentric calcification of the aortic valve on the THV distortion and the relationship between THV distortion and clinical impact were not fully understood. Methods . Patients with symptomatic severe aortic stenosis who were undergoing THV implantation were enrolled. Patients underwent preprocedural, postprocedural multislice computed tomography (MSCT), and follow-up transthoracic echocardiogram (TTE). Delta calcium score (ΔCS) is defined as the difference between the maximum and minimal calcium scores of the three cusps, while valve distortion score (VDS) is defined as the difference between the longest and shortest stent frame, as obtained using MSCT. Patients were divided into two groups according to ΔCS: "noneccentric calcification group" and "eccentric calcification group." Results . A total of 118 patients were enrolled (59 patients in noneccentric and 59 in eccentric calcification groups). VDS was significantly lower in the noneccentric calcification group than in the eccentric calcification group (1.31 ± 0.82 mm vs. 1.73 ± 0.76 mm, p = 0.004 ). VDS was not associated with the degree of paravalvular leak (PVL) and aortic valvular mean pressure gradient (AVPG) at 30-day and 1-year follow-up TTE and the cumulative rates of all-cause death and rehospitalization at 2-year clinical follow-up. Conclusions . Eccentric valvular calcification was associated with longitudinal THV distortion. However, THV distortion was not associated with PVL, AVPG, and adverse clinical events during midterm follow-up.